2019
DOI: 10.1108/tr-02-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

The role of culture personality and self-congruity in the evaluation of cultures as destinations

Abstract: Purpose This study aims to determine cultures as personalities and investigates whether similarities or dissimilarities compared to the respondent’s own personality (actual self) are more attractive. The objectives are to identify the culture personality dimensions relevant for destination choice and to investigate the effect of congruity between perceived actual self and perceived culture personality on the evaluation of the examined cultures as ideal destinations. In this manner, numerous participants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…In most cases, travellers take time to determine whether a destination's personality suits their self-concept; some like to experience tourism products and services personally before evaluating their purchases. Although a plethora of studies (Usakli and Baloglu, 2011;Liu et al, 2012;Chen and Phou, 2013;Xie and Lee, 2013;Kumar, 2016;Chua et al, 2019;Gyulav ari and Malota, 2019;Yang et al, 2020a, b) have modelled the linkage among destination image, destination personality and self-congruity to predict revisit intention, an integrative model combining gender remains omitted from the tourism literature. Within tourism and hospitality research, gender has been identified as a critical determinant of such behaviour (Han et al, 2017;Jiang and Chen, 2019;Yang et al, 2020a, b;Rasoolimanesh et al, 2021) compared with other demographic variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, travellers take time to determine whether a destination's personality suits their self-concept; some like to experience tourism products and services personally before evaluating their purchases. Although a plethora of studies (Usakli and Baloglu, 2011;Liu et al, 2012;Chen and Phou, 2013;Xie and Lee, 2013;Kumar, 2016;Chua et al, 2019;Gyulav ari and Malota, 2019;Yang et al, 2020a, b) have modelled the linkage among destination image, destination personality and self-congruity to predict revisit intention, an integrative model combining gender remains omitted from the tourism literature. Within tourism and hospitality research, gender has been identified as a critical determinant of such behaviour (Han et al, 2017;Jiang and Chen, 2019;Yang et al, 2020a, b;Rasoolimanesh et al, 2021) compared with other demographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Although a plethora of studies (Usakli and Baloglu, 2011; Liu et al. , 2012; Chen and Phou, 2013; Xie and Lee, 2013; Kumar, 2016; Chua et al , 2019; Gyulavári and Malota, 2019; Yang et al. , 2020a, b) have modelled the linkage among destination image, destination personality and self-congruity to predict revisit intention, an integrative model combining gender remains omitted from the tourism literature.…”
Section: Introductionmentioning
confidence: 99%
“…A háromféle megközelítés nem különíthető el szigorúan egymástól: a vállalatok megtelepedése lakosságot vonz(hat), míg a turisztikai látnivalók nem csak a turisták élményeit gazdagítják; a turisták ugyanakkor a lakosság mindennapjaira is pozitív vagy negatív hatással vannak, például a megnövekedett forgalom révén (Hanna, Rowley 2015;Insch 2011;. A város desztinációként történő értékelésére erősen hathat a desztináció személyiségének megítélése -az az, hogy milyen személyiségjegyek társíthatóak egy desztinációhoz (Gyulavári, Malota 2019). Városok esetében így izgalmas kérdés, hogy azok személyisége mennyire egyezik az adott személy saját magáról alkotott képével.…”
Section: Bevezetésunclassified